MiRNA-based "fitness score" to assess the individual response to diet, metabolism, and exercise. Issue 1 (31st December 2022) - Krammer, Ulrike D.B.; Tschida, Sylvia; Berner, Julia; Lilja, Stephanie; Switzeny, Olivier J.; Hippe, Berit; Rust, Petra; Haslberger, Alexander G.
ABSTRACT: Background: Regular, especially sustained exercise plays an important role in the prevention and treatment of multiple chronic diseases. Some of the underlying molecular and cellular mechanisms behind the adaptive response to physical activity are still unclear, but recent findings suggest a possible role of epigenetic mechanisms, especially miRNAs, in the progression and management of exercise-related changes. Due to the combination of the analysis of epigenetic biomarkers (miRNAs), the intake of food and supplements, and genetic dispositions, a "fitness score" was evaluated to assess the individual response to nutrition, exercise, and metabolic influence. Methods: In response to a 12-week sports intervention, we analyzed genetic and epigenetic biomarkers in capillary blood from 61 sedentary, healthy participants (66.1% females, 33.9% males, mean age 33 years), including Line-1 methylation, three SNPs, and ten miRNAs using HRM and qPCR analysis. These biomarkers were also analyzed in a healthy, age- and sex-matched control group (n, 20) without intervention. Food frequency intake, including dietary supplement intake, and general health questionnaires were surveyed under the supervision of trained staff. Results: Exercise training decreased the expression of miR-20a-5p, −22-5p, and −505-3p (p < 0.02) and improved the "fitness score, " which estimates eight different lifestyle factors to assess, nutrition, inflammation, cardiovascular fitness, injury risk, regeneration, muscle and hydration status, as well as stress level. In addition, we were able to determine correlations between individual miRNAs, miR-20a-5p, −22-5p, and −101-3p (p < 0.04), and the genetic predisposition for endurance and/or strength and obesity risk ( ACE, ACTN3, and FTO ), as well as between miRNAs and the body composition (p < 0.05). MiR-19b-3p and −101-3p correlated with the intake of B vitamins. Further, miR-19b-3p correlated with magnesium and miR-378a-3p with iron intake (p < 0.05). Conclusions: In summary, our results indicate that a combined analysis of several biomarkers (miRNAs) can provide information about an individual's training adaptions/fitness, body composition, nutritional needs, and possible recovery. In contrast to most studies using muscle biopsies, we were able to show that these biomarkers can also be measured using a minimally invasive method.